Pelatihan Teknik Editing Video Iklan Menggunakan Adobe Premiere SMK Swasta Pulo Brayan Darat Kecamatan Medan Timur - Dani Manesah; Suryanto; Muhammad Ramadani (Yayasan Kajian Riset Dan Pengembangan Radisi, 2022)
The use of Adobe Premiere as one of the editing software in editing an advertisement video is currently very much needed for students, especially students of SMKS Brayan Darat. With the rapid development of technology at this time, making video advertisements is easy, especially with the Adobe Premiere software, by using this software, making advertisements can be attractive and have an aesthetic impression for the viewer. Smks Pulau Brayan Darat is one of the educational units with the SMK level in Pulo Brayan Darat I, Kec. East Medan, Medan City, North Sumatra. In carrying out its activities, the Pulau Brayan Darat Vocational School is under the auspices of the Ministry of Education and Culture. But unfortunately at this time there are still some students who do not really understand how to operate a computer. So most of them are still new to understanding video editing using Adobe Premiere. It is hoped that this community service activity can be useful for students of SMKS Pulau Brayan Darat in using Adobe Premier software.